JOINT CONFIGURATION OF BACKBONE AND LOGICAL NETWORKS ON A RECONFIGURABLE PACKET-SWITCHED NETWORK WITH UNRELIABLE LINKS - LEE, JONG HYUP; SUNG, CHANG SUP (Engineering optimization, 1998)
This paper considers a problem of configuring both backbone and logical networks in a reconfigurable packet-switched network where links are subject to failures. The objective is to design feasible backbone and logical networks at least cost where the network cost includes backbone link capacity expansion cost and average packet delay penalty cost due to link failures. The problem is formulated as a zero-one non-linear mixed integer programming problem, for which an effective solution procedure is developed by using a Lagrangean relaxation technique for finding a lower bound and a heuristic method is exploited for improving the upper bound of an intermediate solution. The solution procedure is tested for its effectiveness with various numerical examples.